Notes on Early Land Plants Today. 31. Lophonardia replaces Hypolophozia (Cephaloziellaceae, Marchantiophyta) - Söderström, Lars; Váňa, Jiří; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
Several segregates from Lophozia (Dumortier 1831: 53) Dumortier (1835: 17) s. lat. (e.g. sensu Schuster 1969) are now recognized as distinct genera. Bakalin elevated Lophozia subgen. Hypolophozia to Hypolophozia and transferred Lophozia dusenii as Hypolophozia dusenii. Váňa in Engel & Gradstein (2003) synonymized Lophonardia caespitosa with Lophozia laxifolia, which is the type of the genus Hypolophozia. At the genus level Lophonardia has priority over Hypolophozia, so the former name has to be used. It should be noted that although heterotypic synonyms, both genera have the same “accepted” taxon as type.